Ziprasidone as Adjunct Therapy to Mood Stabilizers for the Treatment of Bipolar I Disorder - Sinclair, Heather Q. (MD Conference Express, 2010)
When used as adjunctive treatment to the mood stabilizers lithium or valproate, ziprasidone was equally effective in stabilizing mild to moderately ill subjects and severely ill subjects with bipolar I disorder (BP I). In a Phase III, randomized, double-blind, placebo-controlled trial that evaluated the efficacy of adjunct ziprasidone therapy with a mood stabilizer in the long-term maintenance treatment of BP I, patients were stratified according to baseline illness severity (as determined by Mania Rating Scale score).